2022
DOI: 10.1177/21501319221074117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Acne in Primary Care Patients Assessed Through Teledermatology

Abstract: Introduction/Objectives: Acne is present in about 90% of teenagers and 12% to 14% of adults. Face and trunk are the most affected areas. Lesions can result in postinflammatory hyperpigmentation and scarring, leading to reduced quality of life. Asynchronous teledermatology has been increasingly used around the world, facilitating patient access to dermatologists. Our objectives were to assess: (1) clinical features of acne patients according to gender, age, severity, site of lesions, excoriation, postinflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Studies have shown that the diagnosis of acne is effectively diagnosed through teledermatology 12 . Similarly, in a study involving 2,459 patients using the teledermatology method, the diagnosis of acne was 99% accurate 13 . In our study, there was 100% agreement between the diagnoses of both physicians in all the acne patients.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that the diagnosis of acne is effectively diagnosed through teledermatology 12 . Similarly, in a study involving 2,459 patients using the teledermatology method, the diagnosis of acne was 99% accurate 13 . In our study, there was 100% agreement between the diagnoses of both physicians in all the acne patients.…”
Section: Discussionmentioning
confidence: 92%
“…Dalam salah satu penelitian juga disebutkan adanya kecenderungan jenis kelamin perempuan dengan derajat keparahan akne vulgaris yaitu pada rentang usia 11-13 tahun namun tidak pada usia 14-16 sampai dengan 17 (8). Hal ini berbeda dengan penelitian Bianchi yang menyatakan bahwa akne vulgaris pada perempuan umumnya terjadi pada rentang usia 25-60 tahun dan pada laki-laki sebagian besar terjadi pada usia 13 dan 24 tahun (9). akne lebih berat pada remaja akhir dibandingkan dengan remaja yang masih muda.…”
Section: Pembahasanunclassified